Akuntabilitas Pengelolaan Keuangan Dana Desa Berbasis Website di Desa Terapung Kecamatan Mawasangka Kabupaten Buton Tengah - Armin; Andi Tenri; Abidin, Zainul (Faculty of Social and Political Science, 2024)
The purpose of this study is to clarify Terapung Village's Website-Based Village Fund Financial Management's accountability. This study takes a qualitative and descriptive approach. Interviewing, observation, and documentation methods were used to gather data. Through data preparation, organization, reduction, and presentation, data approaches were examined. The findings demonstrated that Terapung Village, Mawasangka District, Central Buton Regency's village fund administration was not entirely responsible. Permendagri Number 20 of 2018 about Village Financial Management and the Regulation of the Minister of Villages concerning Priorities for the Use of Village Funds, which are established annually, serve as guidelines for the Terapung Village Government's village financial management. Nonetheless, the Regional Government, through the Community and Village Empowerment Office, imposes penalties on the management of village funds in the form of reprimands, delays in the distribution of village fund transfers, and even the Inspectorate of Central Buton Regency authorizes the return of certain funds. There are existing and clear outputs. Everything that is done is the needs of the community according to the results of the village deliberation and the results are benefit to the community. The Terapung Village Government hasn't yet assessed the initiatives' results, though. since it is not yet possible to determine with certainty how the fund management will turn out.